Digital Marketing Analysis of MSMEs in Bantul District: COM-B Model Approach - Dihan Adum Suryoko; Wahyu Tri Wibowo; Romi Bhakti Hartarto (Universitas Ahmad Dahlan, Yogyakarta, 2023)
Progress Internet growth in Indonesia is currently growing rapidly. Shopping activities that previously mostly occurred in traditional markets and supermarkets, with the internet, shopping activities also occur on online buying and selling platforms. This study then contributes to determine the effect of digital marketing on the sales turn over of SMEs in Bantul Regency. Data collection in this study was carried out through semi-structured interviews conducted in-depth on five digital marketing users in Bantul Regency using the Capability, Opportunity, Motiva, and Behavior (COM-B) model to analyze the factors that support and hinder MSME actors from adopting digital marketing. This study found that MSME actors have realized the benefits of using digital marketing. Meanwhile, the lack of digital marketing media used by MSME actors is an obstacle for MSME actors to maximizing sales turnover. Therefore, there is a need for additional training programs.